Developing a Community of Inquiry using an educational blog in higher education from the perspective of Bangladesh - Chowdhury, Sabbir Ahmed; Siddique, Mohammad Nure Alam (Frontiers in Education, 2024)
Web 2.0 tools such as blogs, wikis, social networking, podcasting etc. have received concentration in educational research over the last decade. Blogs enable students to reflect their learning experiences, disseminate ideas, and participate in analytical thinking. The Community of Inquiry (CoI) framework has been widely utilized in educational research to understand and enhance online and blended learning environments. There is insufficient research evidence to demonstrate the impact of educational blogging utilizing the CoI model as a framework. This paper explores how blogs can be used to support collaborative learning and how such interaction upholds CoI through enhancing critical thinking and meaningful learning in the context of Higher Education (HE). An exploratory mixed method research approach has been followed in this study. A convenience sampling method was employed to choose 75 undergraduate students from Dhaka University for a 24-week blogging project. Every publication on the blog was segmented into meaningful units. Whole texts of posts and comments are extracted from the blog and the transcripts are analyzed in Qualitative manner considering CoI framework, more specifically, through the lens of cognitive, social, and teaching presence. In addition, the semi-structured questionnaire is used to collect data from students whether blogging expediated students' learning or not. The research findings indicate that cognitive presence, namely the exploration component, is dominant in blog-based learning activity. Moreover, this research has demonstrated that blogs build reliable virtual connections among students through exchanging ideas and information and by offering opportunities for reflective practice and asynchronous feedback. This study also revealed challenges related to blogging in the context of developing countries, including lack of familiarity with blogs, restricted internet connectivity, limited access to devices, and low levels of social interaction. It is recommended that different stakeholders including policy makers, curriculum developers and teachers may take the initiative to synchronize the utilization of educational blogs with the formal curriculum, guaranteeing that blog activities supplement and improve traditional teaching-learning activities.